IMPACT OF AGE AND GENDER ON LEFT VENTRICULAR THROMBUS FOLLOWING MYOCARDIAL INFARCTION IN ADULTS (40-70 AGE) AT TERTIARY CARE HOSPITAL LRH PESHAWAR (The Research of Medical Science Review, 2025)
Background: Myocardial infarction, a common manifestation of coronary artery disease, stands as a significant contributor to global mortality and morbidity. It categorizes into ST elevation myocardial infarction (STEMI) and non-ST elevation myocardial infarction (NSTEMI), determined by electrocardiogram (ECG) assessments. A prevalent and serious complication of myocardial infarction is the occurrence of a left ventricular thrombus, notably linked with anterior wall myocardial infarction. Objectives: To investigate the association of left ventricular thrombus development with various age groups, genders, and types of myocardial infarction. The objective is to identify which age group, gender, and type of myocardial infarction are more susceptible to developing left ventricular thrombus. Methods: During the period from June to November 2023, a cross-sectional study was undertaken within the Department of Cardiology at Lady Reading Hospital, Peshawar. Data acquisition employed a predefined, self-structured questionnaire, and statistical analysis was performed using SPSS version 23. Results: The study comprised 174 patients: 111 (63.8%) males and 63 (36.2%) females. Among STEMI patients, 84 (48.3%) had anterior wall MI, 60 (34.5%) had inferior wall MI, 3 (1.7%) had posterior wall MI, 12 (6.9%) had high lateral wall MI, and 8 (4.6%) had post MI. Left ventricular thrombus was identified in 31 patients with anterior wall MI and 7 patients with inferior wall MI. The Chi- square test revealed a statistically significant association between left ventricular thrombus and male gender, as well as anterior wall MI. Conclusion: The study concludes that male gender and anterior wall myocardial infarction are significantly associated with the development of left ventricular thrombus compared to female gender and other types of myocardial infarction.